A combined numerical-experimental approach to analyzing fracture initiation and development in brittle rocks. (May 2022) - Kumar Verma, Rupesh; Nguyen, Giang D.; Karakus, Murat; Taheri, Abbas; Bui, Ha H.
Abstract: This paper presents a combined numerical-experimental approach to investigating crack initiation and development in brittle rocks. A three-dimensional dis-continuum based numerical modeling technique is used where rock specimens are idealized as an assembly of deformable tetrahedral blocks interacting via cohesive-frictional contacts. A new cohesive-frictional contact model is developed and implemented in the software 3DEC by Itasca to capture realistic material behavior at grain scale under different loading conditions. The proposed cohesive-frictional contact model model is based on a unified damage-friction criterion that evolves with damage towards a frictional behavior, with effects of damage on dilation behavior to capture evolving contact conditions between rough surfaces. In conjunction with the numerical development are laboratory experiments using Digital Image Correlation (DIC) technique to provide experimental data to validate numerical simulation results at both specimen and local scales. The potentials of the proposed approach in capturing rock responses at both scales are demonstrated.